Squamos cell carcinoma in the fornix of the oral vestibule - Ratajek-Gruda, Monika; Białkowska- Głowacka, Jolanta; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
The article describes a case of a long-term squamous cell carcinoma in the fornix of oral cavity. Diagnostic methods for this medical condition are also described.